2017
DOI: 10.1107/s1600576717000309
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and optical study of PbHfO3 crystals

Abstract: This article details the use of birefringence imaging microscopy and high-resolution X-ray diffraction for determining the symmetries of the phases in PbHfO3 between room temperature and 870 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Within the quality of our X-ray data we cannot comment on the observation of the intermediate polar phase inside the existence field of the incommensurate phase (Bussmann-Holder et al, 2015). As expected, the orthorhombic symmetry we observe is consistent with birefringence measurements (Huband et al, 2017). The (P-T) phase diagram was traced (Samara, 1969(Samara, , 1970 on the basis of dielectric measurements, and it was shown that above ambient pressure one more (denoted as ) phase develops between the paraelectric Pm3m and an intermediate-temperature [incommensurate AFE(II)] phase.…”
Section: Discussionsupporting
confidence: 71%
“…Within the quality of our X-ray data we cannot comment on the observation of the intermediate polar phase inside the existence field of the incommensurate phase (Bussmann-Holder et al, 2015). As expected, the orthorhombic symmetry we observe is consistent with birefringence measurements (Huband et al, 2017). The (P-T) phase diagram was traced (Samara, 1969(Samara, , 1970 on the basis of dielectric measurements, and it was shown that above ambient pressure one more (denoted as ) phase develops between the paraelectric Pm3m and an intermediate-temperature [incommensurate AFE(II)] phase.…”
Section: Discussionsupporting
confidence: 71%
“…The SrHfO 3 thin films were grown from targets with the same nominal composition. For SrHfO 3 , 30-400-nm-thick films were deposited on multiple substrates [i.e., SrTiO 3 (001), SrTiO 3 (110), and NdScO 3 (110)] at a range of heater temperatures (600-850 °C), across various dynamic oxygen-partial pressures (1-100 mTorr), laser fluence values (0.75-2.5 J cm −2 ), and laser repetition rates (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The composition of the Pb 1−x Sr x HfO 3 thin-film heterostructures was varied across 0 < x < 1 through sub-unit-cell-level mixing using two ceramic targets with composition PbHfO 3 and SrHfO 3 via a programmable target rotator (Neocera, LLC) that was synced with the excimer laser.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Among the range of materials that could be studied, two potentially exciting hafnate perovskite oxides are PbHfO 3 and SrHfO 3 . PbHfO 3 (Pba2, lattice parameters: a = 5.854 Å, b = 11.694 Å, c = 8.191 Å [12] ) has been synthesized and its structural, [13,14] optical, [15] and dielectric [16] properties have been probed in bulk ceramics and single crystals. It exhibits a switching-field-induced phase transition from an antiferroelectric Pbam to a ferroelectric Pba2 phase at ≈250 kV cm −1 , characterized by a double polarizationhysteresis loop.…”
mentioning
confidence: 99%
“…Lead hafnate, PbHfO 3 (PHO), which is isostructural with PZO, is known to naturally have such IC phases at ambient conditions. [13][14][15][16][17] Crystallographic and dielectric studies showed that the low-temperature phase of PHO is also antiferroelectric (A1) with space group Pbam, whereas the high-temperature paraelectric (P) phase is cubic, Pm-3m. The above-mentioned IM (A2) is observed between 430 and | 5991 JANKOWSKA-SUMARA et Al.…”
Section: Introductionmentioning
confidence: 99%
“…473 K. Several publications were devoted to establishing the proper structure of this phase. [16][17][18] Based on the latest findings, the symmetry of this phase was established to be orthorhombic, with IC modulations and with Imma(00γ)s00 super-space group. 18 However, the problem of mechanisms responsible for the phase transitions observed is still subject to investigation.…”
Section: Introductionmentioning
confidence: 99%